2023
DOI: 10.3389/fpls.2023.1146658
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of macronutrients for improved grain yield of quinoa (Chenopodium quinoa Wild.) crop under semi-arid conditions of Morocco

Abstract: In the context of climate change, quinoa represents a potential alternative crop for increasing crops diversity, agricultural productivity, and farmer’s income in semi-arid regions. However, appropriate crop management practices under limited water supply are still poorly documented. Quinoa, like other cultivated crops, needs optimum quantities of nutrients, especially nitrogen (N), phosphorus (P), and potassium (K), for better growth and high grain yield. To determine the adequate levels of nutrient requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…This study also found a positive correlation between yield per plant and 1000-grain weight. Previous research has mentioned a positive correlation of yield with seed size, harvest index, and 1000-grain weight [20,31,32]. On the other hand, the number of effective branches at maturity decreased with increasing yield, consistent with the results of Woo et al [19].…”
Section: Structural Equation Modeling Of Yield and Agronomic Traitssupporting
confidence: 84%
“…This study also found a positive correlation between yield per plant and 1000-grain weight. Previous research has mentioned a positive correlation of yield with seed size, harvest index, and 1000-grain weight [20,31,32]. On the other hand, the number of effective branches at maturity decreased with increasing yield, consistent with the results of Woo et al [19].…”
Section: Structural Equation Modeling Of Yield and Agronomic Traitssupporting
confidence: 84%